EFEKTIVITAS PROGRAM APLIKASI SALAMAN DALAM PELAYANAN ADMINISTRASI KEPENDUDUKAN DI DISDUKCAPIL KOTA BANDUNG - Aprilia Azizah; Dewi Rostyaningsih; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Disdukcapil of Bandung City implements the Salaman application program to provide convenience for the community in population administration services. The Salaman application program is one of the innovations created by Disdukcapil to improve public services that utilize information technology through e-government. However, there are still many people in Bandung who do not know about the application and there are still problems found by the community whe using the Salaman application program. The study aims to analyze the effectiveness and constraints of the Salaman application program. The research method used is a qualitative approach. The focus of this research is studied using 3 criteria for program effectiveness according to Budiani in Primanda (2017: 5), namely socialization, objectives and program monitoring. Data collection techniques include interviews, observation and documentation. The results of the field research show that the effectiveness of the Salaman application program, namely (a) program socialization, especially socialization at the regional level, has not run optimally because the communication process has not gone well, (b) program objectives can be said to be effective because all objectives have been achieved as a whole and (c) program monitoring can be said to be effective because Disdukcapil conducts daily supervision, conducts monitoring every quarter and coordination with Diskominfo Bandung City. Furthermore, the obstacles found are related to infrastructure and human resources.